A graphene quantum dots–glassy carbon electrode-based electrochemical sensor for monitoring malathion - Sanju Tanwar; Aditi Sharma; Dhirendra Mathur (Beilstein Journal of Nanotechnology, 2023)
Graphene quantum dots (GQDs) were made via a hydrothermal process with glucose as a precursor undergoing carbonization. Different spectroscopic techniques were used to analyze the optical characteristics of GQDs, including UV–visible, photoluminescence, FTIR, and Raman spectroscopy. Atomic force microscopy, transmission electron microscopy, and X-ray diffraction were used to characterize the morphological and structural properties of GQDs. An electrochemical sensor was developed by drop casting GQDs on a glassy carbon electrode (GCE). The sensor detects the organophosphate pesticide malathion in a selective and sensitive manner. Using cyclic voltammetry, the sensor’s oxidation–reduction behavior was investigated. Electrochemical impedance spectroscopy was conducted to study the electrochemical properties of the modified the GQDs/GCE working electrode, which showed excellent charge transfer properties. We measured malathion in varying concentrations between 1 to 30 µM using differential pulse voltammetry, which resulted in a limit of detection of 0.62 nM. GQDs can thus be used to develop electrochemical sensors for the detection of pesticides in water.